Pembelajaran Berdiferensiasi dalam Meningkatkan Hasil Belajar Fisika Murid kelas X-A SMAN 3 Pandeglang pada Materi Energi Terbarukan - Suhartini, Heni (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2023)
This research is motivated by the importance of learning methods to improve physics learning outcomes in renewable energy materials. The research was carried out using the classroom action research method. This class action research was planned in three cycles. Each cycle is carried out through two face-to-face sessions in class learning, including tests to find out student learning outcomes. The subjects of this study were students in class X-A Semester 1 of SMA Negeri 3 Pandeglang for the 2022-2023 academic year, which consisted of 36 students. The instrument used in this research is test questions. Based on the results of the preliminary study, the results of studying Physics on renewable energy material averaged 78.75 (Beginning to Develop), with the lowest score being 68.00 and the highest being 88.50. The learning outcomes of the first cycle are known that the highest value = 90.00 and the lowest value is 74.50, while the average value is 81.08 (already developed). The learning outcomes of the second cycle are known that the highest value = 93.00 and the lowest value is 77.5 while the average value is 84.89 (already developed). The results showed that the application of the differentiated learning method could improve the physics learning outcomes of class X-A students at SMA Negeri 3 Pandeglang. The application of different learning methods can increase interest and response in the physics learning process in class X-A SMA Negeri 3 Pandeglang